The path towards a truly holistic and comprehensive development of the individual, the society and the nation in this age of turbulence - Hassan, Mohd. Kamal (2015)
Looking at the state of the world and the environment today, we recall what Alan Greenspan, the former Chairman of the Federal Reserve Board of U.S.A. wrote in 2007, namely The Age of Turbulence: Adventures in a New World (Penguin Books 2007). Although his focus was on the financial tumult of recent times, particularly in the U.S.A., the title of his work is an apt description of the current state of economic and financial turmoil, the political uncertainties, social upheavels, moral degeneration and potential environmental catastrophes. In view of these highly challenging global scenarios, a fundamental review of the well-established conventional systems have to be undertaken by Muslim leaders, intellectuals and scholars if the Muslim world and communities are not to remain hostage to the provenly corrupt and unreliable internal and external structures. The modern concept of development, as an important component of the project of secular modernity and the worldview of materialistic progress, has been subjected to intense intellectual and political debates over the last five decades, not only because it is open to a variety of ideological interpretations, but also because its implementation in the Third World or the South has failed to deliver the promises of prosperity, equity, socioeconomic justice and freedom to the masses. Evidences of widening inequalities within the economically developing countries and the alarming ecological crisis of planet earth point undoubtedly to serious faults in modern man’s economic and technological exploitation of natural and human resources. If one were to take into consideration the recent symptoms of dangerous systemic breakdown of Western economic and financial systems as well as the moral decay of modern culture, one wonders how much longer the Third World should remain subservient to the dominant paradigm of Godless modernity and unethical progress. In the Muslim world too, it is now evident that nations which followed the path of secular development or the unjust models of economic growth have to contend with strong opposition from the religious-oriented movements and mounting resistance from the educated, the alienated, the oppressed and the impoverished groups of people. The current uprising or social unrest brewing in a number of Middle Eastern societies today has its roots in long-standing economic, social and political discontent which was suppressed by the greedy and autocratic leaders whose strong grip on the political system was, nonetheless, endorsed and sustained by the Western promoters of democracy and human rights themselves. It seems that the intelligent and the educated Arab youths and intelligentsia could no longer bear the hypocrisy of national leaders and the hypocrisy of international forces of global hegemony. The way forward can no longer be the destructive path of soul-denying development, but the less trodden path of holistic material-spiritual development of man, society, culture and state.